2020
DOI: 10.1536/ihj.19-372
|View full text |Cite
|
Sign up to set email alerts
|

Destructive Role of TMAO in T-Tubule and Excitation-Contraction Coupling in the Adult Cardiomyocytes

Abstract: Heart failure (HF) is a disease with high morbidity and mortality. In patients with HF, decreased cardiac output and blood redistribution results in decreased intestinal perfusion and destruction of intestinal barrier. Microorganisms and endotoxins can migrate into the blood circulation, aggravating systemic inflammation and HF. Trimethylamine N-oxide (TMAO) is highly closed to the occurrence of HF. However, the exact mechanism between TMAO and HF remains unclear. To investigate the role of TMAO in transverse-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 40 publications
1
9
0
1
Order By: Relevance
“…This leads to a decrease in contraction amplitude, longer time of peak and reduced synchronization. 21 Similar TMAO-induced abnormalities in contractility were also reported in ex-vivo human cardiac tissue. 22…”
Section: Direct Cardiotoxic and Proarrhythmic Effects Of Tmaosupporting
confidence: 62%
“…This leads to a decrease in contraction amplitude, longer time of peak and reduced synchronization. 21 Similar TMAO-induced abnormalities in contractility were also reported in ex-vivo human cardiac tissue. 22…”
Section: Direct Cardiotoxic and Proarrhythmic Effects Of Tmaosupporting
confidence: 62%
“…Savi et al found that TMAO promotes the release of calcium ions in cardiac muscle cells of healthy mice and thus alters their contractility [ 95 , 96 ]. Recently, the in-depth work carried out by Jin et al showed that TMAO confers detrimental effects on adult cardiomyocytes by inducing T-tubule network damage and Ca handling dysfunction [ 97 ]. When TMAO was administered to HF mice, Organ et al found that mouse cardiac function deteriorated significantly, characterized by pulmonary oedema, cardiac enlargement, and decreased ejection fraction [ 98 ].…”
Section: Implications Of Gut Microbiota In Cvdsmentioning
confidence: 99%
“…TMAO has been positively correlated with enhanced atherosclerosis [74,75] and cholesterol-laden macrophage foam cell formation [76], platelet hyper-reactivity (through calcium release), and increased thrombosis potential, vascular inflammation, and inflammasome activation [77][78][79]. Consequently, numerous large-scale clinical cohorts have established the vital involvement of TMAO in many CVD phenotypes, such as coronary artery disease (CAD) [80], heart attack and ischemic stroke [81,82], heart failure [83,84], acute coronary syndrome [80], and peripheral artery disease [85]. Bile acids are also responsible for the modulation of certain diseases, as we have already discussed above.…”
Section: Gut Metabolitesmentioning
confidence: 99%